How can process-based modeling improve peat CO2 and N2O emission factors for oil palm plantations? - Swails, E.; Hergoualc'h, Kristell; Deng, J.; Frolking, S.; Novita, N. (Elsevier, 2022)
Oil palm plantations on peat and associated drainage generate sizeable GHG emissions. Current IPCC default emission factors (EF) for oil palm on organic soil are based on a very limited number of observations from young plantations, thereby resulting in large uncertainties in emissions estimates. To explore the potential of process-based modeling to refine oil palm peat CO2 and N2O EFs, we simulated peat GHG emissions and biogeophysical variables over 30 years in plantations of Central Kalimantan, Indonesia. The DNDC model simulated well the magnitude of C inputs (litterfall and root mortality) and dynamics of annual heterotrophic respiration and peat decomposition N2O fluxes. The modeled peat onsite CO2-C EF was lower than the IPCC default (11 Mg C ha−1 yr−1) and decreased from 7.7 ± 0.4 Mg C ha−1 yr−1 in the first decade to 3.0 ± 0.2 and 1.8 ± 0.3 Mg C ha−1 yr−1 in the second and third decades of the rotation. The modeled N2O-N EF from peat decomposition was higher than the IPCC default (1.2 kg N ha−1 yr−1) and increased from 3.5 ± 0.3 kg N ha−1 yr−1 in the first decade to 4.7–4.6 ± 0.5 kg N ha−1 yr−1 in the following ones. Modeled fertilizer-induced N2O emissions were minimal and much less than 1.6% of N inputs recommended by the IPCC in wet climates regardless of soil type. Temporal variations in EFs were strongly linked to soil C:N ratio and soil mineral N content for CO2 and fertilizer-induced N2O emissions, and to precipitation, water table level and soil NH4+ content for peat decomposition N2O emissions. These results suggest that current IPCC EFs for oil palm on organic soil could over-estimate peat onsite CO2 emissions and underestimate peat decomposition N2O emissions and that temporal variation in emissions should be considered for further improvement of EFs.